Effect of different media and pH on growth and sporulation of Fusarium oxysporum f.sp. lentis causing wilt of lentil - SANJEEV KUMAR*, PRIYANKA SINGH and (Indian Phytopathology, 2016)
Laboratory studies were conducted to study the effect of different culture media, and pH on mycelia growth, sporulation and dry mycelia weight of Fusarium oxysporum f.sp. lentis The fungus grew the best on PDA and Richard’s agar media among five culture media were tested. The most suitable pH level for growth of fungus was 6.5 and 7.0 with excellent sporulation.